Behaviour Of Bamboo Reinforcement In Flexural Strength Of Sea Water Concrete Slab - Alamsyah Alamsyah; Hery Waluyo; Muhammad Zulkarnain; Faisal Ananda; Zev Aljauhari (Journal of Green Science and Technology, 2019)
World Resources Institute data shows that there will be a fresh water crisis in 2040 including Indonesia. Responding to the above, many studies have been carried out using seawater, one of which is on concrete. Several studies have shown that seawater does not reduce the quality of concrete, but provides a corrosion effect on reinforcement.In this study, sea water concrete slabs have been made using bamboo as a reinforcement that will not corrode due to seawater. For concrete mix design refers to SNI SNI 03-2834-2000 and for slab flexural strength refers to 03-2847-2002. Slab specimens with sea water concrete that have been made consist of Slab concrete of steel reinforcement (SCS), Slab concrete of bamboo reinforcement V type notch (SCBV)Â  and Slab concrete of bamboo reinforcementÂ  U type notch (SCBU).The result of the compressive strength of sea water concrete can reach the compressive strength of the plan. Tensile strength of bamboo reaches 223.5MPaand approaching the tensile strength of steel reinforcement. The maximum load of SCBV and SCBU were decrease than theoretical analysis of0.14% and 21.51% respectively. Otherwise, the maximum load of SCS greater than theoretical analysis with a difference of 14.67%. The flexural strength of the concrete slab was not affected by sea water as in compressive strength of cylinder.Keywords: Bamboo reinforcement slab, Flexural strength, Seawater concrete